Financial reforms and international trade - Munasib, Abdul; Roy, Devesh; Chen, Xing (Walter de Gruyter GmbH, 2014)
We provide evidence that financial reforms (over 1976–2005) significantly affected exports, in particular, of industries with higher external capital dependence and low asset tangibility. The coverage of reforms is comprehensive, encompassing the banking sector, interest rates, equity and international capital markets. Our methodology improves upon existing studies by controlling for time-varying unobserved exporter characteristics and unobserved country-specific industry characteristics. We find significant effects of various reforms with diverse impacts by intensity. Further, event studies that incorporate possible anticipated and lagged effects of commencement of reform policies confirm the findings.